Coral da multiplicidade - Duarte, Priscila Nery [UNESP]; Quinta, Andressa Rodrigues Martins da [UNESP]; Elstermann, Anna Katharina [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
In 2014, the Coral da Multiplicidade (Multiplicity Choir) was acknowledged as an extension project of the Department of Modern Languages of UNESP Assis. In the years before, it was part of another project called Clinic@rte, organised by the Department of Psychology. As an extension project, the choir does not only work with the internal staff of university (students, teachers and technical staff) but also with the external community, such as public schools in the region, in order to promote the social inclusion of members independently of their economic and ethnic origins. Through the motivational group work and the jointly reached finalization of songs, the singers also overcome their personal limitations and, consequently, improve in expressing their feelings, thus bringing more lightness to tribulations of their lives. Therefore, besides criticising normative and contradictory factors of our society through the music, which strengthen inequalities and social weaknesses, the project’s main intention is to build a more egalitarian world which accepts the differences and origins of each person.

No ano de 2014, o Coral da Multiplicidade consolidou-se como um projeto de extensão do Departamento de Letras Modernas. Antigamente ele fazia parte do projeto Clinic@rte junto ao Departamento de Psicologia Clínica. Dessa forma passou a desenvolver, a partir do canto-coral, um trabalho comunitário não só dentro da FCL-Assis como também em escolas públicas da região, a fim de motivar a inserção social dos integrantes, independentemente de seus marcadores sociais de diferença, tais como raça/etnia, nível socioeconômico, sexo, gênero e orientação sexual. Por meio do incentivo e realização do trabalho em equipe, o desafio em aprender uma nova canção reflete-se na superação de limites individuais e, consequentemente, proporciona uma melhor expressão dos sentimentos e, posicionamento crítico sobre os processos de subjetivação que nos compõem. Assim, a partir da música, além de criticar os fatores normativos e homogeneizados da nossa sociedade que fortalecem as desigualdades e inequidades sociais, o projeto tem como intuito construir um mundo mais igualitário que não apenas aceite as diferenças, mas que também as estimule.
Keywords: Choir singing; Social inclusion; Equality; Canto-coral; Inserção social; Igualdade